NILAI ETIS PERUSAHAAN DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - Widaryanti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
In this article, we learned about ethical theory. First, Corporate Ethical Index and empirically assess the impact of corporate ethical identity (CEI) on a firm’s financial performance (market-to-book values). Drawing on formulations of normative and instrumental stakeholder theory, we argue that firms with a strong ethical identity achieve a greater degree of stakeholder satisfaction (SS), which, in turn, positively influences a firm’s financial performance. We analyze dimensions of the CEI of firms applied ethics. Our results indicate that whereas applied ethics hasn’t an impact through the improvement of firm performance.